Molecular Connectivity Index Based Aqueous Solubility Prediction Model - HU, YANG-DONG; WANG, YING-LONG (Asian Journal of Chemistry, 2010)
Correlations for estimation of the aqueous solubility (log Sw) of organic compounds are proposed. The MCI based models proposed are predictive and require only zeroth- and first-order connectivity indices in the calculations. The calculated results of the models for different data sets are comparable to those from the existing models. Because the new models do not require any experimental physicochemical properties in the calculation, they can be used in cases where it-is too dangerous, costly, time consuming or impossible to measure the physico-chemical properties. Furthermore, the obtained equations can be easily applied in computer-aided molecular design for its simplicity and linear formula.